Optimizing Polyhydroxyalkanoate Production Potential from VFA-Rich Landfill Leachate under Limited Phosphorus Availability - Ulutug, Fatma Cansu; Ciftcioglu-Gozuacik, Bengisu; Keskinler, Bülent; Karagündüz, Ahmet (Springer, 2025)
The conventional landfill leachate treatment processes focus on mineralizing carbonaceous material have high operational cost. However, leachates contain value added compounds including ammonia and volatile fatty acids (VFAs). The conversion potential of VFA into polyhydroxyalkanoates (PHA) biopolymer was examined to achieve environmentally friendly, efficient, and cost-effective landfill leachate treatment in the study. A pretreatment using Mechanical Vapor Recompression (MVR) evaporator was performed to recover volatile fatty acids, which were then used as a carbon source for mixed microbial culture. The effect of VFA concentration (700 mg VFA/L, 1400 mg VFA/L and 2000 mg VFA/L) and phosphorus-limited conditions (C/P: 100/3, 100/1.5, 100/0.75) were investigated to maximize PHA yield. A remarkable PHA storage (73%) was achieved under optimum conditions. The thermophysical properties of the obtained PHA was compared with standard PHA. The hybrid treatment of landfill leachate combining MVR and biotechnological PHA production offers efficient and cost-effective treatment with 1.23 USD/m3 net profit.
Keywords: Landfill Leachate; Biopolymer; Volatile Fatty acid; Mixed Microbial Culture; Polyhydroxyalkanoate